Comparative Physiological and Proteomic Analyses Reveal the Mechanisms of Brassinolide-Mediated Tolerance to Calcium Nitrate Stress in Tomato - Zhang, Yi; Chen, Haoting; Li, Shuo; Li, Yang; Kanwar, Mukesh Kumar; Li, Bin; Bai, Longqiang; Xu, Jin; Shi, Yu (Frontiers in Plant Science, 2021)
Secondary salinization caused by overaccumulation of calcium nitrate [Ca(NO3)2] in soils due to excessive fertilization has become one of the major handicaps of protected vegetable production. Brassinolide (BR, a bioactive plant steroid hormone) plays an important role in improving abiotic stress tolerance in plants. However, whether and how BR can alleviate Ca(NO3)2 stress remains elusive. Here, we investigated the effects of exogenous BR on hydroponically grown tomato (Solanum lycopersicum L.) plants under Ca(NO3)2 stress through proteomics combined with physiological studies. Proteomics analysis revealed that Ca(NO3)2 stress affected the accumulation of proteins involved in photosynthesis, stress responses and antioxidant defense; however, exogenous BR increased the accumulation of proteins involved in chlorophyll metabolism and altered the osmotic stress responses in tomato under Ca(NO3)2 stress. Further physiological studies supported the results of proteomics and showed that exogenous BR-induced alleviation of Ca(NO3)2 stress was associated with the improvement of photosynthetic efficiency, levels of soluble sugars and proteins, chlorophyll contents and antioxidant enzyme activities, leading to the reduction in the levels of reactive oxygen species and membrane lipid peroxidation, and promotion of the recovery of photosynthetic performance, energy metabolism, and plant growth under Ca(NO3)2 stress. These results show the importance of applying BR in protected agriculture as a means for the effective management of secondary salinization.